The Impact of Formal Mentorship Programs on Mentorship Experience Among Radiation Oncology Residents From the Northeast - Sayan, Mutlay; Ohri, Nisha; Lee, Anna; Abou Yehia, Zeinab; Gupta, Apar; Byun, John; Jabbour, Salma K.; Wagman, Raquel; Haffty, Bruce G.; Weiner, Joseph; Kim, Sung (Frontiers in Oncology, 2019)
Purpose: Strong mentorship has been shown to improve mentee productivity, clinical skills, medical knowledge, and career preparation. We conducted a survey to evaluate resident satisfaction with mentorship within their radiation oncology residency programs. Methods and Materials: In January 2019, 126 radiation oncology residents training at programs in the northeastern United States were asked to anonymously complete the validated Munich Evaluation of Mentoring Questionnaire. Results of residents with a formal mentoring program were compared to those without a formal program. Results: Overall response rate was 42% (n=53). Participants were 25% post-graduate year two (PGY-2), 21% PGY-3, 26% PGY-4, and 28% PGY-5. Only 38% of residents reported participation in a formal mentoring program, while 62% had no formal program, and 13% reported having no mentor at all. Residents participating in a formal mentoring program reported strikingly higher rates of overall satisfaction with mentoring compared to those who were not (90% vs 9%, p<0.001). Overall, 38% of residents were either satisfied/very satisfied with their mentoring experience, while 49% of residents were unsatisfied/very unsatisfied. Conclusion: Residents participating in a formal mentorship program are significantly more likely to be satisfied with their mentoring experience than those who are not. Our results suggest that radiation oncology residency programs should strongly consider implementing formal mentorship programs.